Analisis Pengaruh Return On Assets (ROA), ReturnOn Equity (ROE), Dan Debt to Equity Ratio (DER)Terhadap Dividend Payout Ratio(Studi pada Perusahaan Manufaktur yang Terdaftar di BursaEfek Indonesia Periode 2012-2014) - Utami, Novia Candra, Dra. Wuryaningsih Dwi Lestari, M.M (2016)
The purpose of this research is to analyzes the effect of Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio Dividend payout ratio (empirical study on manufacturing companies listed in Indonesia Stock Exchange Year 2012 to 2014) show that simultaneously and partially. Sampling method that is used is purposive sampling and there are 23 sample companies that will be research objects. The analytical techniques used is multiple linear regression analysis by using SPSS where the data was tested using the coefficient of determination, test F, t test of the significant level is 5%. Furthermore the data was tested using the classical assumptions in terms of The independence variables in this research are financial performance in terms of normality test, multikolinearitas test and heterokedastisitas test. Return On Assets (ROA), Return On Equity (ROE), and Debt to Equity Ratio (DER), and while Dividend Payout Ratio as dependent variable. The results of this research show that simultaneously, all of independent. variables have significant effect to the value of the firm. Partially, Return On Assets (ROA) and Return On Equity (ROE) had positive effect and significant to Dividend Payout Ratio (DPR), while Debt to Equity Ratio (DER) had negative effect and not significant to Dividend Payout Ratio (DPR).